DISTRIBUTION OF ONE-PHASE FLUID FLOW IN THE SILINDER TUBE - DIA MUHSIN (NIM : 10212070), IRFAN
Fluid is a substance that always experience deformation when it is did by forces or pressures. Fluid also can be defined as substance that always undergoing deformation. The velocity profile of fluid divided into three types. They are a laminar flow, transition flow, and turbulent flow. In fluid mechanics, there are some equations that can describe the form of velocity profile. This equations as well know as Navier-Stoke’s equation. There are two of equations that always be used in fluid flow problem. One is continuity equation and other is momentum equation. From this equations, it able to get other quantities such as shear stress,eddy current, mixing length, average velocity, space’s flow every time, friction factor, head loss, and power of pump. For this equation if it is did in analytical solution, it need long time to be solved. For that, it need numerical solution with computation. Finite difference method is one from other numerical solution that can did it easily. One of finite difference method is called FTCS method. This method is easy to be used.